Geometry, spatial arrangement and origin of carbonate grain-dominated, scour-fill and event-bed deposits: Late Jurassic Jubaila Formation and Arab-D Member, Saudi Arabia - Jacquemyn,C; Jackson,MD; Hampson,GJ; John,CM; Cantrell,DL; Zhlke,R; AbuBshait,AJ; Lindsay,RF; Monsen,R (Sedimentology, 2018)
Outcrop analogues of the Late Jurassic lower Arab-D reservoir zone in Saudi Arabia expose a succession of fining-upward cycles deposited on a distal middle-ramp to outer-ramp setting. These cycles are interrupted by erosional scours that incise up to 1·8 m into underlying deposits and are infilled with intraclasts up to boulder size (1 m diameter). Scours of similar size and infill are not commonly observed on low-angle carbonate ramps. Outcrops have been used to characterize and quantify facies-body geometries and spatial relationships. The coarse grain size of scour-fills indicates scouring and boulder transport by debris or hyperconcentrated density flows strengthened by offshore-directed currents. Longitudinal and lateral flow transformation is invoked to produce the ‘pit and wing’ geometry of the scours. Scour pits and wings erode up to 1·8 m and 0·7 m deep, respectively, and are on average 50 m wide between wing tips. The flat bases of the scours and their lack of consistent aspect ratio indicate that erosion depth was limited by the presence of cemented firmgrounds in underlying cycles. Scours define slightly sinuous channels that are consistently oriented north–south, sub-parallel to the inferred regional depositional strike of the ramp, suggesting that local palaeobathymetry was more complex than commonly assumed. Weak lateral clustering of some scours indicates that they were underfilled and reoccupied by later scour incision and infill. Rudstone scour-fills required reworking of material from inner ramp by high-energy, offshore-directed flows, associated with storm action and the hydraulic gradient produced by coastal storm setup, to generate erosion and sustain transport of clasts that are generally associated with steeper slopes. Quantitative analysis indicates that these coarse-grained units have limited potential for correlation between wells as laterally continuous, highly permeable rese